Spatial Pricing Patterns in the United States - Greenhut, John; Greenhut, M. L.; Li, Sheng-Yung (Quarterly Journal of Economics, 1980)
This paper is an empirical extension of spatial price theory with results being established by selected statistical approaches, namely multiple linear regression and Chow's test. The locational pattern of competitors as well as varying intensities of competition at different spatial market points are found to play dominant roles in determining the pricing patterns of American firms. Differences in the price practices of firms of different states are identified, and price discrimination over geographic space is found to be the most prevalent pricing technique.